The Effect of E-Monitoring Tools on Changes in Family's Degree of Dental and Mouth Health In The Community Of Meunasah Manyet Village, Aceh Besar - Reca; Intan Liana (Science Midwifery, 2022)
Adolescent dental health is an important thing that is often neglected in the family. Family dental nursing care can help resolve family health problems in adolescents. This study aims to determine the effect of e-monitoring tools on changes in the degree of dental and oral health of families in the community in Meunasah Manyet village, Aceh Besar. This research method is quasi-experimental l. The subjects in this study were 60 teenagers, then divided into two groups, the intervention group (monitoring with e-monitoring tools and providing home visit services) consisted of 30 people, and the control group consisted of 30 people who were not given intervention ( only sheet monitoring manual and dental health education). Analysis of the data results (quantitative) in this study used paired sample t-test and independent t-test. The results showed that there was an effect of e-monitoring tools on changes in the degree of family dental and oral health ( Knowledge, Attitudes, and Actions) in the community in Meunasah Manyet Aceh Besar village (p<0.05). The use of e-monitoring tools as a tool/media to change adolescent behavior in a positive direction, of course, still prioritizes persuasive parenting patterns to children.